Brazilian immigration in Portugal: State and power relations - Ibiapina Alves, Mary Help (Argumentum, 2025)
Recently, migratory determinants of countries in the global North have shifted public opinion, policies, and relations between countries and human rights. This article presents the results of a doctoral research project and analyses the relationship between immigration and the mechanisms of State power. It focusses on the living conditions of Brazilian immigrants awaiting regularisation in Portugal. The methodology follows qualitative procedures with a mixed approach, using semi-structured interviews and online questionnaires directed at the immigrant population. Results point to the Portuguese state's governmental tactics that create a bureaucratic limbo, block fundamental rights, and result in the precariousness of immigrant life and citizenship.